Cardiac surgery air-bridging in the Caribbean (2020)
The need for air-bridging of cardiac patients in the Caribbean for surgical treatment abroad has many downfalls. Besides the burden on national health budgets, the risks involved with transfers, and delayed treatment, patients depend completely on care abroad.